The Naturalness of Figurative Language of ‘The Trials of Apollo: The Hidden Oracle’ Novel - Rizka Alma Sari; Rudi Hartono (Universitas Negeri Semarang, 2022)
The concept of equivalent refers to how closely a language's source and target work in a certain situation. By rating or evaluating a translation's quality, the translator can decide whether it is natural. This study aims to explain the naturalness of the Indonesian translation of the figurative language contained in the novel ‘The Trials of Apollo: The Hidden Oracle.’ In order to collect data, the researchers obtained words, phrases, clauses, and sentences that contained figurative language. Leech's (1969) classification of figurative language and Larson's (1998) assessment of the naturalness of translation were used in the analysis of the data, which was done using the content analysis technique. This study measures the naturalness of translation in order to enhance translation rather than criticize the translator. This study identified four levels of naturalness for figurative translation: highly natural level, natural level, less natural level, and unnatural level. It was revealed that the translator offered a highly natural figurative translation. It indicates that the translator succeeded in making the content understandable and making it clear to the reader, preventing readers from realizing the text is a translation. The quality of the natural translation must be evaluated in order to deliver a better translation that will aid the target audience in comprehending the book's content.